Apolipoprotein C-II Deposition Amyloidosis: A Potential Misdiagnosis as Light Chain Amyloidosis - Sadichhya Lohani; Emily Schuiteman; Lohit Garg; Dhiraj Yadav; Sami Zarouk (Case Reports in Nephrology)
Hereditary amyloidoses are rare and pose a diagnostic challenge. We report a case of hereditary amyloidosis associated with apolipoprotein C-II deposition in a 61-year-old female presenting with renal failure and nephrotic syndrome misdiagnosed as light chain amyloidosis. Renal biopsy was consistent with amyloidosis on microscopy; however, immunofluorescence was inconclusive for the type of amyloid protein. Monoclonal gammopathy evaluation revealed kappa light chain. Bone marrow biopsy revealed minimal involvement with amyloidosis with kappa monotypic plasma cells on flow cytometry. She was started on chemotherapy for light chain amyloidosis. She was referred to the Mayo clinic where laser microdissection and liquid chromatography mass spectrometry detected high levels of apolipoprotein C-II, making a definitive diagnosis. Apolipoprotein C-II is a component of very low-density lipoprotein and aggregates in lipid-free conditions to form amyloid fibrils. The identification of apolipoprotein C-II as the cause of amyloidosis cannot be solely made with routine microscopy or immunofluorescence. Further evaluation of biopsy specimens with laser microdissection and mass spectrometry and DNA sequencing of exons should be done routinely in patients with amyloidoses for definitive diagnosis. Our case highlights the importance of determining the subtype of amyloidosis that is critical for avoiding unnecessary therapy such as chemotherapy.